Concrete admixtures handbook : properties, science, and technology - Ramachandran, V. S. (Noyes Publications, 1995)
The increased role and development of admixtures in concrete technology is evidenced by a number of conferences, publications, and novel admixtures available in the market place. Admixtures are not as inert as may be presumed. They may chemically interact with the constituents of concrete and affect the properties of the fresh and hardened concrete and its durability.
Keywords: Concrete -- Additives.; elektronické knihy; electronic books